الميتافيروس كأداة لتغيير سلوك المستهلك السياحي الرقمي: Metaverse as a tool for changing the behaviour of the digital tourism consumer - أحلام زايد,; كمال زموري,; إيمان زايد, (Journal of North African Economies, 2025)
The study seeks to address some concepts associated with metaverse and its role in changing the behaviour of the digital tourism consumer The aim of this study was to highlight metaverse as a new concept and tourism experiences and to reveal disruptions in tourists' behaviour and experiences while in metaverse, The analytical descriptive approach was followed, and the study found that Metaverse world is now clearly coming and tourism will not escape this global trend. It has come to stimulate more physical travel, and it can also meet the utilitarian needs of tourist customers to experience before actually buying.